Speed synchronization, physical workload and match-to-match performance variation of elite football players - Gonçalves, Bruno (2019)
This study aimed to: (i) examine whether the speed synchronization and physical perfor- mance of an elite football team changed between the first and the second half, using match time blocks of 15-min, and (ii) explore the match-to-match variation of players’ speed syn- chronization performance. Twenty-eight outfield elite footballers participated in 51 official matches. Positional data were gathered and used to calculate the total distance covered as a physical workload indicator. For all the outfield teammate dyad combinations (45 pairs), it was processed the percentage of time that players’ speed was synchronized during walking, jogging and running using relative phase (Hilbert Transform). Also, the match-to-match vari- ation of the players’ speed synchronization, expressed in coefficient of variation was com- puted. The differences in the total distance covered from all players within the different match’s time block periods revealed a moderate decrease in the distance covered in the last 15-min of the match compared to the first 15-min (-6.5; ±1.07%, most likely: change in means with 95% confidence limits). However, when compared the last minutes from both halves a small increase was observed (2.7; ±1.2%, likely) from first to second half. The syn- chronization of the players’ speed displacements revealed small to moderate decreases in the % of synchronization in the second half periods for the jogging and running speed, while the opposite was found for the walking speed (~13 to 24% more, most likely). The playing position analysis for the walking zone showed similar trends between the groups, with small to moderate higher values in the second half, with the exception of [30’-45’] vs [75’-90’] in the midfielder’s dyads and in [15’-30’] vs [60’-75’] match periods for forwards. Similar trend was found during the running speed, in which small to moderate higher synchronization was found during the first half periods, with the exception of [15’-30’] vs [60’-75’] and [30’-45’] vs [75’-90’] in midfielder’s dyads. Regarding to the match-to-match variation of the players’ speed synchronization, overall results showed small to moderate increases in coefficient of variation during jogging and running displacements from the beginning to the end of the match (32.1; ±13.2% increase in jogging and 26.2; ±10.5% in running, both comparisons most likely). The higher distance covered during most of the first half periods and the higher dyadic synchronization at high speeds might have limited players’ performance in the second half. In addition, the decrease trend in speed synchronization during the second half periods might have resulted from accumulated muscular and mental fatigue towards the match. Within, the match-to-match variation in tactical-related variables increased across the match duration, with especial focus in the midfielder dyads. Dyadic speed synchroniza- tion might provide relevant information concerning the individual and collective performance.